La tutela dei diritti umani nel bacino del Mediterraneo - Galgano, Francesca (Cultura delle differenze: Diritto, conoscenza, formazione, 2021)
The book collects the voices of a wide-ranging debate on human rights in the Mediterranean basin and on the current declinations of their protection with regard to migrants, women, lawyers, prisoners, asylum seekers. The resulting dialogue is only one of many possible, but it sometimes reveals unprecedented implications, always abundant in suggestions full of pathos, on our present and above all on our future.